ESENSI TRANSPARANSI DAN AKUNTABILITASI DALAM PENDAFTARAN TANAH DALAM SISTEM HUKUM INDONESIA - D N M Sahari, Deselfia (Al-Ishlah: Jurnal Ilmiah Hukum, 2018)
The essence of transparency and accountability in land registration within the legal system in Indonesia has not been realized properly. Due to the weakness of the guarantee of legal certainty and legal protection from the government. In addition, the publication system of land registration adopted is negative with a positive tendency, not applied in Article 32 paragraph (2) of Government Regulation Number 24 Year 1997 regarding expiration to file a five-year lawsuit there is a synchronization / non-harmonization concerning land authority between local government Article 14 paragraph (2 ) Letter k of Law Number 23 Year 2014 regarding Regional Government and Authority of National Land Agency (Regulation of Head of National Land Agency No.2 Year 2013 regarding Abundance of Land Rights and Land Registration Authority) and regulation of grace period of entitlement right. AbstrakEsensi transparansi dan akuntabilitas dalam pendaftaran tanah dalam sistem hukum di Indonesia belum terealisasi dengan baik. Karena lemahnya jaminan kepastian hukum dan perlindungan hukum dari pemerintah. Selain itu, sistem publikasi pendaftaran tanah yang diadopsi negatif dengan kecenderungan positif, tidak diterapkan dalam Pasal 32 ayat (2) Peraturan Pemerintah Nomor 24 Tahun 1997 tentang berakhirnya pengajuan gugatan lima tahun ada sinkronisasi / non-harmonisasi tentang kewenangan pertanahan antar pemerintah daerah Pasal 14 ayat (2) Huruf k Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah dan Kewenangan Badan Pertanahan Nasional (Peraturan Kepala Badan Pertanahan Nasional No.2 Tahun 2013 tentang Kelimpahan Hak atas Tanah dan Pendaftaran Tanah Otoritas) dan peraturan masa tenggang hak cipta. Kata kunci: Transparansi; Akuntabilitas; Pendaftaran Tanah; Sistem Hukum;